Macronutrient intake and triglyceride levels in overweight late adolescents in an Islamic boarding school - Damayanti, Amilia Yuni; Hamidah, Fildzah Haya; Fathimah, Fathimah; Pibriyanti, Kartika (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2025)
Background: Being overweight has become an epidemic health problem worldwide. The prevalence of overweight and obesity in the Islamic boarding school was 20.92%. It occurs due to an imbalance in food intake that affects the body's metabolism, resulting in the accumulation of fat in the blood and an increase in triglyceride levels.Objective: This study aimed to determine the relationship between macronutrient intake and triglyceride levels in overweight adolescents in an Islamic boarding school.Methods: This type of research employed observational analysis using a cross-sectional design. The research was conducted at Universitas Darussalam Gontor from November 2022 to February 2023. The study included 50 female students aged 17 to 25 years. BMI of overweight measurements using digital weight scales of the GEA medical brand type EB 9360 and microtoise types of portable stadiometer brands. Macronutrient intake was determined using the 24-hour food recall method, and triglyceride levels were measured using Pictus 400 with Wiener brand reagent for laboratory tests. The statistical test used was the gamma test.Results: The majority of respondents were found to have a lower macronutrient intake, while 44% had more than adequate intake, and 38% had a higher carbohydrate intake. For protein intake, most respondents (90%) were categorized as having excessive intake. Similarly, for fat intake, some respondents (88%) were also categorized as having excessive intake. The results of examining triglyceride levels in the respondents' bodies showed that 88% had normal triglyceride levels and 12% had abnormal levels. The gamma test showed that the p-value of carbohydrate intake with triglyceride levels was p = 0.166, for protein intake with triglyceride levels, p = 0.051, and for fat intake with triglyceride levels, p = 0.037.Conclusions: A relationship was found between fat intake and triglyceride levels. But, there was no significant relationship between carbohydrate and protein intake and triglyceride levels.